GAMBARAN PENGETAHUAN SIKAP DAN PERILAKU PADA PENDERITA DBD DI WILAYAH KERJA PUSKESMAS BAWANG 1 - Mawar Rafiyanti; Joko Malis Sunarno (Jurnal Ilmiah Medsains, 2025)
Dengue Hemorrhagic Fever (DHF) remains a public health issue in Indonesia. In 2024, a total of 210,644 cases were reported, including 94 cases in the working area of UPTD Bawang 1 Health Center from January to March 2025. This highlights the importance of understanding community behavior in controlling DHF. This study aims to describe the knowledge, attitudes, and practices of DHF patients as a basis for prevention strategies.This research is a descriptive study with a cross-sectional approach, conducted in May–June 2025 involving 49 DHF patients selected using random sampling. Data were collected through questionnaires, observations, and secondary data from the health center. Univariate analysis was used to assess the frequency distribution of each variable.The results showed that most patients were female (61.2%), aged between 12–25 years, and were students. The majority of respondents had good knowledge (69.4%), positive attitudes (95.9%), and positive practices (98%) related to DHF prevention.In conclusion, DHF patients in the UPTD Bawang 1 Health Center area demonstrated good knowledge and behavior in preventing DHF. The health center is expected to collaborate with village authorities in formulating policies related to population mobility to help prevent the spread of DHF.